Evaluation on the Stability of Amine-Mesoporous Silica Adsorbents used for CO2 Capture - Viet Quang, Dang; Duong, Dao Van; Hong Ha, Vu Thi; Duc, Dao Sy; Ngoc Dung, Tran Thi; Abu-Zahra, Mohammad R.M. (VNU Journal of Science: Earth and Environmental Sciences; Vol 36 No 1, 2020)
Amine-mesoporous silica has been considered as a promising CO 2 adsorbent with high potential for the reduction of energy consumption and CO 2 capture cost; however, its stability could greatly vary with synthetic method. In this study, adsorbents prepared by impregnating different amines including polyethylenimine (PEI) and 3-aminopropyltriethoxysilane (APTES) onto mesoporous silica were used to evaluate the effect of amines selection on the stability of adsorbents used in CO 2 capture process. Results revealed that APTES impregnated mesoporous silica (APTES-MPS) is more stable than PEI-impregnated mesoporous silica (PEI-MPS); APTES-MPS was thermally decomposed at ≈280 o C, while PEI-MPS was thermally decomposed at ≈180 o C only. PEI-MPS was particularly less stable when operating under dry condition; its CO 2 adsorption capacity reduced by 22.1% after 10 adsorption/regeneration cycles, however, the capacity can be significantly improved in humid condition. APTES-MPS showed a greater stability with no significant reduction in CO 2 capture capacity after 10 adsorption/regeneration cycles. In general, APTES-MPS adsorbent possesses a higher stability compared to PEI-MPS thanks to the formation of chemical bonds between amino-functional groups and mesoporous silica substrate. Keywords: Mesoporous silica; CO 2 capture; Adsorption; Regeneration; Emission.